Excessive gestational weight gain and emotional eating are positively associated with postpartum depressive symptoms among taiwanese women - Chia-Hsun Wu; Meei-Ling Gau; Su-Fen Cheng; Tzu-Ling Chen; Chih-Jung Wu (BMC, 2023)
Abstract Background Excessive gestational weight gain and emotional eating may be associated with postpartum depression symptoms. This study was designed to identify how gestational weight gain and eating behaviors are related to postpartum depression (PPD) symptoms among women in Taiwan. Methods A cross-sectional study was conducted from March 2022 to October 2022 with 318 postpartum women recruited in Taipei, Taiwan. Gestational weight gain (GWG) for the total pregnancy period was recorded as inadequate, adequate, or excessive, based on the 2009 Institute of Medicine recommendations (IOM), accounting for pre-pregnancy body mass index category. Eating behavior at one month postpartum was measured on a 16-item 5-point Likert scale with three subscales: uncontrolled, restrained, and emotional. Maternal depressive symptoms were measured using the Edinburgh Postnatal Depression Scale with a cutoff score of 13. Results The prevalence of postpartum depression symptoms (Edinburgh Postnatal Depression Scale ≥ 13) was 23.9% at one month postpartum. Logistic regression analysis revealed that excessive gestational weight gain and emotional eating were positively associated with postpartum depression symptoms at that time. Conclusion Evidence presented here suggests that emotional eating and excessive GWG are associated with PPD symptoms in a Taiwanese population. In addition, it should be a public health priority to ensure a particular focus on mental health during the postpartum period. Healthcare providers should discourage pregnant women from unhealthy eating habits by targeting appropriate GWG and focusing on demand eating to reduce PPD in the postpartum period.